2008
DOI: 10.1111/j.1468-2362.2008.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Targeting in a Small Open Economy*

Abstract: In this paper we offer a justification for the observed wide variation in monetary practices across industrial countries. We claim that differences in the monetary policy rule adopted may simply reflect differences in economic structure and, in particular, in the types of shocks encountered and nominal rigidities present in various countries. We find that a case for inflation targeting can be made when external shocks are the prevalent source of volatility in the economy -a likely scenario for a small open eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, due to the volatility of trade-offs between variables, a simple comparison of volatilities does not straightforwardly identify the regime that delivers the highest level of macroeconomic stability. As Cuche-Curti, Dellas, and Natal (2008) summarize, an exchange rate peg can outperform a flexible exchange rate regime under the assumptions of a stable external environment and that the main source of nominal rigidity is in the goods market. They also find that policies ignoring movements in the exchange rate can be dominated by a simple exchange rate targeting policy.…”
Section: Macroeconomic Stabilitymentioning
confidence: 92%
See 2 more Smart Citations
“…However, due to the volatility of trade-offs between variables, a simple comparison of volatilities does not straightforwardly identify the regime that delivers the highest level of macroeconomic stability. As Cuche-Curti, Dellas, and Natal (2008) summarize, an exchange rate peg can outperform a flexible exchange rate regime under the assumptions of a stable external environment and that the main source of nominal rigidity is in the goods market. They also find that policies ignoring movements in the exchange rate can be dominated by a simple exchange rate targeting policy.…”
Section: Macroeconomic Stabilitymentioning
confidence: 92%
“…A focus on macroeconomic stability is used as the standard approach to the evaluation of monetary policy. This approach simplifies the analysis because of its independence of the welfare function specification, and it offers interesting comparisons, as presented by Cuche-Curti, Dellas, and Natal (2008) and Collard and Dellas (2002).…”
Section: Macroeconomic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent studies have shown that monetary policy regimes such as in ‡ation targeting can play a role in dampening cyclical macroeconomic ‡uctuations and improve welfare in small open economies (see e.g. Svensson, 2000;Cuche-Curti et al, 2008). The choice of monetary policy regimes also matters because wages and prices of non-tradable goods are sticky in the short-run and the speed at which relative prices adjust depends crucially on the monetary policy regime.…”
Section: Introductionmentioning
confidence: 99%